Incident cardiovascular events and risk of subsequent cancer diagnosis. (25th November 2020) - Fardman, A; Oppenheim, A; Banschick, G.D; Rabia, R; Segev, S; Klempfner, R; Fourey, D; Percik, R; Grossman, E; Maor, E
Abstract: Background: Cardiovascular disease (CVD) and cancer share common risk factors. This study investigated the association of CVD diagnosis and the risk of future cancer. Methods: We evaluated asymptomatic self-referred adults aged 40–79 years who participated in a screening program. All subjects were free of CVD and cancer at baseline. CVD was defined as the composite of acute coronary syndrome, percutaneous coronary intervention or stroke. Cancer and mortality data were available for all subjects from national registries. Primary end-point was development of cancer during follow up. Cox regression models were applied with CVD as a time-dependent covariate and death as a competing risk event. Results: Final study population included 15, 486 subjects. Median age was 50 years (Interquartile range [IQR] 44–55) and 72% were men. During median follow up time of 11 years (IQR 6–15) 1, 028 (7%) subjects developed CVD, 1, 281 (8%) developed cancer and 499 (3%) died. Most common cancer types were prostate among men (N=277, 1.8%) and breast among women (N=187, 1.2%). Time dependent survival analysis showed that subjects who developed CVD during follow up were 60% more likely to develop cancer (95% Confidence Interval [CI] 1.3–1.95, p<0.001). However, after adjustment for known predictors of cancer, the association of incident CVD with cancer diagnosis was no longer significant (p=0.21). Interaction analysis demonstrated that the association of incident CVD with the risk of future cancer diagnosis was age dependent such that in younger subjects (<50 years; N=7, 649) incident CVD was associated with a significant 2 fold increased risk of subsequent cancer diagnosis (95% CI 1.2–3.6, p=0.014) while in older subjects incident CVD was not associated with increased risk of cancer in the multivariable model (p for interaction =0.035; Figure 1). Conclusions: Incident CVD is independently associated with 2-fold increased risk of subsequent cancer diagnosis among young adults. Our analysis underscores the importance of cancer surveillance among young patients following a CVD event. Funding Acknowledgement: Type of funding source: None